Liquisolid Technology: A Novel Concept - Khan, Imran; Arjariya, Priyanka; Sharma, Chandrakant; Sahni, Sumit; Sharma, Garima; Gupta, Varsha (Asian Journal of Pharmaceutical Research and Development, 2017)
Most of the drugs that have been invented are BCS Class II. This technique of delivering drugs is suitable mostly for lipophilic drugs and poorly water soluble drugs and enhance the immediate or sustain release formulations. Increase in dissolution rate and in turn improvement in bioavailability is observed in case of poorly water soluble drugs. Therefore; dissolution rate enhancement is the key aspect for absorption of these drugs. Liquisolid technology is very efficient in the dissolution rate enhancement of these drugs. Moreover use of the other polymers such as Eudragit and Hydroxypropyl Methylcellulose in the Liquisolid approach can cause sustained release of drugs.Liquisolid system is evaluated by flow behavior, wettability, powder bed hydrophilicity, saturation solubility, drug content, differential scanning calorimetry, Fourier transform infra red spectroscopy, powder X-ray diffraction, scanning electron microscopy, in vitro release and in vivo evaluation. Liquisolid serve as a better technique in the controlled release formulations of poorly water soluble drugs.